Regarding the evidence-based use of micronized progesterone - A. D. Makatsariya; G. C. Di Renzo; G. Rizzo; V. O. Bitsadze; J. Kh. Khizroeva; D. V. Blinov; E. I. Vovk; I. E. Govorov; D. L. Guryev; G. B. Dikke; M. S. Zainulina; N. S. Zakharova; et al. (Акушерство, гинекология и репродукция, 2020)
An issue of habitual miscarriage poses a high social importance especially during COVID-19 pandemic. Meanwhile, healthcareworkers faced a mass media campaign against using micronized progesterone upon habitual miscarriage, which, as viewed by us, displays signs of prejudiced data manipulation and may disorient practitioners. In this Letter we provide objective information on accumulated data regarding gestagenes efficacy and safety. We invoke healthcare professionals to make decisions deserving independent primary source trust presented by original scientific papers published in peer-reviewed journals, clinical recommendations proposed by professional medical communities as well as treatment standards and protocols.